PERANCANGAN FILM ANIMASI GARUDEYA MELALUI ALIH WAHANA RELIEF CANDI SUKUH - Adisukma, Wisnu (Universitas Dian Nuswantoro, 2024)
The study was done in order to produce animation that would serve as a medium for the Sukuh Temple's Garudeya relief and provide cultural awareness for the surrounding archipelago. Media for education and enjoyment has changed as a result of technological advancements in several areas. One of the literary traditions of Indonesia, temple reliefs, are becoming less and less popular among today's youth, particularly in light of the invasion of foreign cultures in Indonesia. The indigenous wisdom found in the temple reliefs of the archipelago provides moral values that are valuable to the current generation, which is why preservation efforts are necessary. It is intended that literacy through technological adaptation will be achieved by turning the animation of the story of Garudeya found on the relief at Sukuh Temple.